Reversible neuropathic pain model created by long-term optogenetic nociceptor stimulation using light-responsive pain mice - Satoshi Kouroki; Toyoaki Maruta; Kotaro Hidaka; Tomohiro Koshida; Mio Kurogi; Yohko Kage; Ayako Miura; Hikaru Nakagawa; Toshihiko Yanagita; Ryu Takeya; Isao Tsuneyoshi (PLoS ONE, 2025)
Neuropathic pain has a significant social impact, with high morbidity and reduced productivity, the underlying mechanisms of neuropathic pain remain poorly understood, and effective therapeutic strategies remain elusive. The development of animal models of neuropathic pain that stimulate only the nociceptors and not the other sensory receptors or motor nerves is desirable for elucidating the complex pathogenesis of neuropathic pain. We have previously reported the generation of NaV1.7−channelrhodopsin-2 (ChR2), NaV1.8−ChR2, and NaV1.9−ChR2 mice. Optogenetics was employed in these light-responsive pain mice for generating nociceptive pain by specifically exciting the spinal dorsal root ganglion neurons, in which the respective Na+ channels are expressed through exposure to blue light. This study aimed to compare the neuropathic pain produced by the prolonged exposure of light-responsive pain mice to blue light. A reversible neuropathic pain state was established persisting for a minimum of 24 hours when each light-responsive pain mouse was irradiated with light of an intensity that consistently elicited pain. Furthermore, the mice also showed pain sensitivity to light irradiation and mechanical stimulation. The expression of c-Fos, a marker for neuronal activity following noxious stimulation, was increased in the dorsal horn of the spinal cord on the light irradiated side. DS-1971a, a selective NaV1.7 inhibitor, was effective in attenuating neuropathic pain in all light-responsive pain mice. In conclusion, optogenetics helps elucidate the specific functions of sodium channel subtypes in pain signaling, thereby advancing our understanding and paving the way for the development of further effective treatments for pain disorders in the future.